2017
DOI: 10.18632/oncotarget.17817
|View full text |Cite
|
Sign up to set email alerts
|

U94 of human herpesvirus 6 down-modulates Src, promotes a partial mesenchymal-to-epithelial transition and inhibits tumor cell growth, invasion and metastasis

Abstract: U94, the latency gene of human herpesvirus 6, was found to inhibit migration, invasion and proliferation of vascular endothelial cells (ECs). Because of its potent anti-migratory activity on ECs, we tested the capability of U94 to interfere with the individual steps of the metastatic cascade. We examined the U94 biological activity on the human breast cancer cell line MDA-MB 231, as a model of highly aggressive cancer cell. Here we show that the expression of U94 delivered by an HSV-1-based amplicon promoted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…HUVECs were isolated, characterized and cultured as previously described [58]. HMVEC-Ls were purchased from Clonetics (San Diego, CA, USA) and cultured in EGM-2MV (Lonza, Milan, Italy) containing 10% FBS.…”
Section: Cell Culturesmentioning
confidence: 99%
“…HUVECs were isolated, characterized and cultured as previously described [58]. HMVEC-Ls were purchased from Clonetics (San Diego, CA, USA) and cultured in EGM-2MV (Lonza, Milan, Italy) containing 10% FBS.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Of interest, the HHV-6A/B gene U94 exhibits anti-tumorigenic effects in some in-vitro carcinoma models. Expression of HHV-6B U94 in breast cancer and cervical cancer cell lines decreased the migration and invasiveness of the cells in vitro , and the injection of U94-expressing cancer cells into mice resulted in reduced tumor growth and more limited vasculature in the resulting tumors ( 173 ). Earlier, HHV-6A was found to reduce lymphangiogenesis and angiogenesis in vitro ( 174 ) and limit migration of endothelial cells ( 174 ) and oligodendrocyte progenitor cells ( 175 ).…”
Section: Potential Mechanisms Of Hhv-6-associated Neoplasiamentioning
confidence: 99%
“…Although the efficiency of HHV-6 infection of ECs in vitro was low, inhibition of angiogenesis was observed in 100% of cells, suggesting that probably it was associated to the expression of a soluble factor, conditioning the angiogenic behavior of all cultured cells 5 . Recently, it was also shown that U94 inhibits tumor driven angiogenesis, decreasing tumor invasion and metastasis 10 .…”
Section: Introductionmentioning
confidence: 99%